Survei Jentik Nyamuk Aedes Aegypti di Wilayah Kerja Puskesmas, Kecamatan Cimahi Utara - Nany Djuhriah; Neneng Yetty Hanurawati; Mimin Karmini; Sadono Setioko (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Hemorrhagic fever is caused by the dengue virus transmitted through the bite of the Aedes aegypi mosquito. This disease increases every year and can affect all age groups. The purpose of this service is to measure the density of larvae in the RW 03 area of Pasirkaliki Village, North Cimahi District. Method: The partner in this activity is RW 01 which includes RT: 01, RT 02, RT 04 with survey and observation methods. Result: RT 01: House Index: 44.4 %, Container Index 24.6%, RT 02: House Index 22.2 %, Container Index: 18.4 %, RT 04: House Index 14.4 %, Container Index 29.7 %, RT 05: House Index : 22.7 % , Container Index: 2.5 %. Density Figure 6 with a value of 69.4%. Conclusion: Breteau Index (BI) RW 03 with Density Figure (DF) 6, because it has a value of 69.4% is included in the high category.